ANALISIS SIKAP SOPAN SANTUN TERHADAP KARAKTER PEDULI SOSIAL SISWA SD NEGERI MAYANGAN - Octaviasari, Salsabila; Rigianti, Henry Aditia; Kurniawati, Wahyu (LPPM Institut Pendidikan Nusantara Global, 2023)
This study uses a type of qualitative descriptive research related to the analysis of politeness towards the socially caring character of elementary school students. The first key informant is the class teacher by conducting an interview process. This study uses observation, interviews, and documentation to collect data. Politeness is a reflection of morals that can be achieved through the learning process at school. Behavior needs to be formed since students are at the Elementary School Education level, because when they are at this level it influences the further development of Education. With the cultivation of polite values to children, it is necessary that the child can socialize well in his social environment. The formation of a social caring character is very important to be instilled from an early age. Through the formation of a social caring character, children are expected to be able to instill life habits to care for and empathize with others, and to always be responsive to friends who are in trouble. This study aims to find out how important polite behavior is to produce socially caring characters in elementary school age children. The results show that politeness in elementary school students can still be developed because politeness will affect the social caring character of individuals.